Factor associated with severity of obstructive sleep apnea in Thammasat University hospital - Wongpradit, Wadee; Kulalert, Prapasri; Sattaratpaijit, Nithita (Asian Medical Journal and Alternative Medicine, 2023)
Introduction: Obstructive sleep apnea (OSA) is a prevalent chronic disease and is associated with many adverse health outcomes, but OSA is underrecognized by physicians. Objectives: To identify factors associated with severity of OSA Methods: This was a retrospective cross-sectional study. 587 OSA patients were enrolled and classified into 3 groups: mild, moderate, and severe OSA. Demographic and comorbidity data, anthropometric measurement, and Epworth sleepiness scale were reviewed. Ordinal regression was used to analyze the associated factors. Results: The prevalence of mild, moderate, and severe OSA were 39.0%, 23.9% and 56.7% respectively. Univariable analyses showed that male sex, body mass index (BMI) > 25 kg/m2, neck circumference (NC) > 40 cm, excessive daytime sleepiness, hypertension, and diabetes mellitus were associated with severity of OSA. Multivariable ordinal analysis showed that age ≥ 60 years old, male sex, BMI ≥ 25 kg/m2, NC > 40 cm, excessive daytime sleepiness, and diabetes mellitus were associated with severity of OSA. Conclusions: Our identifying factors assist to recognize adult patients at risk of OSA by severity.